Vue D’ensemble Sur le Systeme Marocain de Retraite - Ammari, Fadwa (صلاح الدين دكداك, 2016)
The interest of this article is to bring an overview of the birth of pension schemes in Morocco and demographic constraints that affect retirement pension, it would be important to relate the different points to change in the new reform retirement. However, it is still worth reviewing other foreign experiences in this field in order to learn lessons.
Keywords: راتب التقاعد -- المعاشات التقاعدية -- التقاعد المغربى -- التوزيع -- الرسملة